2022
DOI: 10.3389/feduc.2022.961046
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization during the era of COVID-19: An analysis of the psychophysiological strain of university students

Abstract: The pandemic has created a push for changes in education and technology that are driving progress in all areas of instruction. This impetus is forcing all stakeholders to address the transformation of traditional education into online education. This change in the education system requires students and teachers to train new competencies, knowledge, skills, and abilities. In this context, this paper aimed to determine the psychophysiological strain of university students in relation to distance learning during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Virtualization is swiftly proliferating across various facets of our lives. A total of 32 studies were found to be dedicated to the application of virtualization in the realm of education (Affouneh et al, 2021;Alamo et al, 2021;Antón-Sancho et al, 2022;Chamorro-Atalaya et al, 2021;Liu, 2021;Broks, 2020;Díez-Pascual, 2022;Ghadrdoost et al, 2021;Hertling et al, 2022;Pereira et al, 2021;Babieva et al, 2022;Hertrampf et al, 2022), etc. Another 27 studies investigated the development of virtualization in the context of machine learning (Atul, et al, 2019;Mirzaee et al, 2022. In the field of cloud computing, 17 studies scrutinized the trends in virtualization (Al-Yarimi et al, 2022;Hanussek et al, 2021; Furthermore, nine studies focused on the application of virtualization in data centers (Arellano-Uson et al, 2021;Ben-Zvi et al, 2022;Bermejo et al, 2022;Compastié et al, 2020;Fati et al, 2020, etc.…”
Section: Areas Of Development Of Virtualizationmentioning
confidence: 99%
“…Virtualization is swiftly proliferating across various facets of our lives. A total of 32 studies were found to be dedicated to the application of virtualization in the realm of education (Affouneh et al, 2021;Alamo et al, 2021;Antón-Sancho et al, 2022;Chamorro-Atalaya et al, 2021;Liu, 2021;Broks, 2020;Díez-Pascual, 2022;Ghadrdoost et al, 2021;Hertling et al, 2022;Pereira et al, 2021;Babieva et al, 2022;Hertrampf et al, 2022), etc. Another 27 studies investigated the development of virtualization in the context of machine learning (Atul, et al, 2019;Mirzaee et al, 2022. In the field of cloud computing, 17 studies scrutinized the trends in virtualization (Al-Yarimi et al, 2022;Hanussek et al, 2021; Furthermore, nine studies focused on the application of virtualization in data centers (Arellano-Uson et al, 2021;Ben-Zvi et al, 2022;Bermejo et al, 2022;Compastié et al, 2020;Fati et al, 2020, etc.…”
Section: Areas Of Development Of Virtualizationmentioning
confidence: 99%
“…The transformative impact of COVID-19 has driven advances in education and technology, causing all stakeholders to transition from traditional to online education. This shift includes the essential training of students and educators in the capacity, knowledge, skills and abilities pertinent to information education (Babieva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The role of geoinformation technologies and geographic systems, in particular for the formation of subject competences in training professionals in geography, was analyzed by V. V. Leta, M. M. Karabiniuk, R. S. Molikevych, I. V. Kholoshyn, O. V. Bondarenko, M. DeMers, T. Chou, M. Yeh, Y. Lai [12], [13], [14], [15], [16]. The directions of using computer technologies, the analysis of problems and ways to solve them, as well as the consideration of individual programs and services are presented in the works of O. V. Bondarenko and others [17], N. S. Babieva and others [18], R. H. Audet, J. Paris [19]. The theoretical and methodological foundations of distance learning, ways of its implementation, prospects and problems that arose during the COVID-19 pandemic are reflected in the works of many foreign scientists, among whom we can highlight H. Karnatak [20], R. Delling [21], G. Rumble [22], M. Simonson [23], I. Ivanova [24], M. Segbenya [25], I. Pylypenko [26] and others [27].…”
Section: Introductionmentioning
confidence: 99%